2023
DOI: 10.3390/nano13172463
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Various Two-Dimensional Supporting Materials on the Water Electrolysis of Co-Mo Sulfide/Oxide Heterostructure

Ngoc-Diem Huynh,
Won Mook Choi,
Seung Hyun Hur

Abstract: In this study, various two-dimensional (2D) materials were used as supporting materials for the bimetallic Co and Mo sulfide/oxide (CMSO) heterostructure. The water electrolysis activity of CMSO supported on reduced graphene oxide (rGO), graphite carbon nitride (gC3N4), and siloxene (SiSh) was better than that of pristine CMSO. In particular, rGO-supported CMSO (CMSO@rGO) exhibited a large surface area and a low interface charge-transfer resistance, leading to a low overpotential and a Tafel slope of 259 mV (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…This property is also applied in the electrodes used for the oxygen evolution reaction . Owing to this material property, the R ct value decreased. The resistance and capacitance of the modified electrode decreased to 0.36 × 10 –5 and increased 730 times those of the bare electrode (Table ). These changes revealed that the total impedance of the modified electrode at 1 kHz decreased to over 1/10 6 times that of the bare electrode and was 5 kΩ, which is sufficient for neural stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…This property is also applied in the electrodes used for the oxygen evolution reaction . Owing to this material property, the R ct value decreased. The resistance and capacitance of the modified electrode decreased to 0.36 × 10 –5 and increased 730 times those of the bare electrode (Table ). These changes revealed that the total impedance of the modified electrode at 1 kHz decreased to over 1/10 6 times that of the bare electrode and was 5 kΩ, which is sufficient for neural stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The RE was calibrated according to previously established procedures . The potential obtained from the RE (Hg/HgO) was then converted to the standard reversible hydrogen electrode (RHE) using the Nernst equation: E RHE = E Hg/HgO + 0.92 (V).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The RE was calibrated according to previously established procedures. 24 The potential obtained from the RE (Hg/HgO) was then converted to the standard reversible hydrogen electrode (RHE) using the Nernst equation: E RHE = E Hg/HgO + 0.92 (V). Linear sweep voltammetry (LSV) was performed at a scan rate of 5 mV/s in the potential range of 1−1.72 V versus RHE.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For instance, sodium ion-doped, and amorphous Ni 2 P 2 O 7 , and porous Co 2 P 2 O 7 , having different morphologies, were constructed and found to be promising materials in energy storage applications [ 23 ]. Although pyrophosphate-based materials worked well and showed promising electrochemical performance in energy storage devices, it would be ideal to develop a simple and economical way to boost their electrochemical water oxidation performance [ 24 ].…”
Section: Introductionmentioning
confidence: 99%